Failure Assessment of Cracked Pipes Based on Failure Assessment Diagram Considering Random and Fuzzy Uncertainties. (2015) - Wu, W.; Cheng, G.X.; Li, Y.; Zhou, Q.; Hu, H.J.
Abstract: Defects of pressure piping, especially cracks, are inevitable during the lifetime of pipe, which will result in the pipe failure. In order to ensure safe operation of pipe, failure assessment for the pressure pipe containing defects needs to be implemented. In fact, the assessment parameters would show two types of uncertainty: randomness and fuzziness, because of the errors of inspection and lack of precise information. In this paper, a fuzzy-probabilistic failure assessment method has been developed based on Failure Assessment Diagram (FAD) from API 579-1/ASME FFS-1 procedure. This method combines the probability theory with possibility theory to deal with fuzzy and random variables. Also, Monte Carlo simulation is used to calculate the failure probability of pipe. This method was applied to a pipe with a surface crack. The effects of variables and their uncertainties on failure probability were analyzed. The results show that the wall thickness and diameter of the pipe has the most important contribution to the pipe failure, followed by the fracture toughness, the yield strength, the operating pressure, the depth and length of the crack.